2003
DOI: 10.1128/iai.71.9.5219-5224.2003
|View full text |Cite
|
Sign up to set email alerts
|

GastricHelicobacterInfection Inhibits Development of Oral Tolerance to Food Antigens in Mice

Abstract: The increase in the transcellular passage of intact antigens across the digestive epithelium infected with Helicobacter pylori may interfere with the regulation of mucosal immune responses. The aim of this work was to study the capacity of Helicobacter infection to inhibit the development of oral tolerance or to promote allergic sensitization and the capacity of a gastro-protective agent, rebamipide, to interfere with these processes in mice. Oral tolerance to ovalbumin (OVA) was studied in 48 C3H/He 4-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The beneficial effect of rebamipide with respect to the epithelial barrier, already recognized for gastric and small intestinal mucosa [7,17], has now been shown for colonic mucosa. This effect concerns both paracellular and transcellular permeability.…”
Section: Discussionmentioning
confidence: 97%
“…The beneficial effect of rebamipide with respect to the epithelial barrier, already recognized for gastric and small intestinal mucosa [7,17], has now been shown for colonic mucosa. This effect concerns both paracellular and transcellular permeability.…”
Section: Discussionmentioning
confidence: 97%
“…45 The authors also reported that Helicobacter infection inhibits the development of oral tolerance by preventing anti-OVA IgE suppression, normally induced after OVA feeding. 49 Oral tolerance is characterised by induction of a state of systemic immune non-responsiveness towards antigens present in the gastrointestinal tract. [50][51][52] This mechanism presumably prevents the development of food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas these pathogens generally cause a self-limiting diarrheal disease, H. pylori chronically infects the human stomach. Recent studies have shown that H. pylori may allow the transepithelial entry of food antigens, and the infection has been associated with the development of food allergies in some patients (8,15,33,34). Future research will determine if strain-specific gastric barrier disruptions may explain, at least in part, the variable clinical outcomes seen in response to H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, while the host inflammatory response may contribute to an increase in permeability in human subjects (19,38), the ability of the bacterium to directly disrupt tight junctions of the human gastric epithelium remains controversial (2,44). Recent findings showed that H. pylori has the ability to increase the passage of food antigens across human gastric biopsies (33), as well as in animal model systems (34). These observations are consistent with observations that the infection may be associated with the development of food allergy (8,15).…”
mentioning
confidence: 99%